Morphological characterization, histopathological alteration, and cytokine response of different tissues of Columba livia naturally infected with Haemoproteus columbae - Salem, Heba M.; Ibrahim, Amira M.; Barsoum, Sara S.; Mahmoud, Mahmoud A.; Albohiri, Haleema H.; Almayouf, Mina A.; Almutairi, Layla A.; Alqahtani, Mohammed A.; Areshi, Sultan Mohammed; El-Tarabily, Khaled A.; Attia, Marwa M. (Frontiers in Veterinary Science, 2025)
IntroductionHaemoproteus columbae is a common haemosporidian worldwide blood parasite affecting domestic pigeons (Columba livia). Therefore, this study aimed to detect the incidence of H. columbae infection in domestic pigeons with morpho-molecular identification.MethodsIn the current study, blood samples were collected from 125 domestic pigeons between 2023 and 2024 and analyzed using both microscopic and molecular techniques. H. columbae positive birds underwent postmortem (PM) and histopathological examinations, as well as cytokine immunological reaction assessments.ResultsIt was found that around 8% (10/125) of pigeons were positive for H. columbae infection, and their morphological characteristics were reported. H. columbae induces observable macroscopic and microscopic alterations in the infected tissues, which increases the cytokine immunological reaction in the infected birds. The infected birds suffered from severe histopathological changes in most haemopoietic and parenchymatous organs. The transcript levels of inflammatory markers such as IL-6, IFN-γ, and IL-1β were significantly upregulated in H. columbae-infected birds. Additionally, the H. columbae samples’ mRNA level of the apoptotic Cas-3 indicated apoptotic activity.DiscussionHematic parasites can pose a serious health threat to pigeons as they invade red blood cells and internal organs, leading to anemia, weakness, weight loss, and even death in severe cases. Epidemiological studies and surveys are essential for monitoring these hematologic parasites. Furthermore, additional research is recommended to evaluate the efficacy of various herbal extracts in comparison to the most frequently used drugs for managing this issue in affected pigeons.